Screening of Endosymbion Fungus Potential on The Stem of Avicennia sp. from Shore of Bandar Lampung City as an Antibacterial - Susanti, Oktora; Harpeni, Esti; Efendi, Eko; Karima, Nisa; Muamar, Aslam (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Mangroves scattered in the shore of Lampung have considerable potential to be used as medicines and antibiotics, because the distribution of various mangroves on almost every shore of Lampung is overgrown with various mangrove plants. Mangroves have a symbiotic relationship with microbes, so that mangrove endosymbion microbes generally have the same bioactive compounds as their hosts. Mangrove Avicennia sp. is one of the mangrove species that has the ability to be antibacterial. Mangrove endosymbion microbes can also have the ability to inhibit antibacterial pathogens that cause disease. Diseases whose cases are found in the community, one of which is caused by Staphylococcus aureus bacteria and Escherichia coli. The purpose of this study is to screen the potential isolate of the endosymbion fungus Avicennia sp. as an antibacterial against S.aureus and E.coli bacteria. Isolation results of Avicennia sp. 12 isolates of endosymbion fungi were obtained that have inhibitory activity against S. aureus and E. coli. and 5 isolates (WBJ-R01, WBJ-R04, WBJ-R05, WBJ-R09, and WBJ-R12) that had the best inhibitory zone activity. Extracts from the five endosymbion fungi isolates have inhibitory zones in both pathogenic bacteria. It is proven that the five extracts at the highest concentration are in a strong inhibition zone. WBJ-R01, WBJ-R04, WBJ-R05, WBJ-R09, and WBJ-R12 isolates had inhibition zones of 11.4 mm, 11 mm, 11.73 mm, 12.3 mm, and 13.23 mm, against S.aureus bacteria respectively. and against E.coli bacteria 14.03 mm, 10.3 mm, 13.13 mm, 9.73 mm, and 6.5 mm.